Assessment of Growth, Chemical Composition, and Antioxidative Capacity of Coho Salmon (Oncorhynchus kisutch) Alevins Fed Dietary Vitamin A Under Controlled Conditions - Leyong Yu; Hairui Yu; Abdur Rahman; Govindharajan Sattanathan; Han Zhang; Lingyao Li; Shahid Sherzada; Mehnoor Sameer; Muhammad Younus (Fishes, 2025)
Vitamin A (VA) is an essential micronutrient that improves growth, immune activity, and antioxidant responses in fish. This study focuses on optimizing VA dietary levels for Oncorhynchus kisutch (Coho salmon) alevins. A 12-week trial was conducted using seven diets containing graded dietary VA levels of 244, 957, 1902, 3494, 6906, 10,248, and 25,213 IU/kg. A total of 2100 fish were reared in 21 tanks; 100 fish were housed in each tank, and 3 tanks represented one treatment. Peak (SGR) and FBW were observed at 6906 IU/kg. Excess VA levels (>15,000 IU/kg) compromised feed conversion efficacy and led to oxidative stress. Analysis of proximate composition resulted in protein and lipid deposition at optimal VA levels. However, excess may have led to metabolic disturbances and reduced ash content. The activity of the antioxidant enzymes catalase (CA), acid phosphatase (ACP), alkaline phosphatase (AKP), and total superoxide dismutase (T-SOD) revealed biphasic patterns, peaking at 6906 IU/kg and dropping when VA levels were exceeded, inducing pro-oxidant effects. Malondialdehyde (MDA), the indicator of toxicity, had a minimal value of 15,000 IU/kg. VA accumulation in the liver showed a dose-dependent relationship, while excess storage (>25,000 IU/kg) induced hepatotoxicity. Quadratic regression was used to identify the optimum VA levels required in Coho salmon alevins, ranging from 6906 to 10,248 IU/kg. Polynomial quadratic regression results indicated that the predicted dietary inclusion of VA at 3000 IU/kg and 15,000 IU/kg may yield better results of T-SOD and MDA. Real-world experimentation is recommended to explore long-term VA optimization with other nutrients and promote better feed utilization and sustainable aquaculture practices.